Kontektualisasi Shurā dalam Demokrasi (Studi Terhadap Pandangan dan Praktik Demokrasi Kiai dan Santri di Madura) - Zainuddin Syarif (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2020)
The contextualization of shura in democracy can be seen from the extra-curricular activities of the students in the election of the Student Council Chair in educational institutions under the auspices of Islamic boarding schools in Madura. In general, students have recognized and implemented a democratic system and used this in electing leaders in educational institutions. This demonstration party has educated students to accept and participate in all programs planned by the winning contestants at the democratic party at educational institutions which are held every year. The kaintan with this is that the students have carried out the requirements to become leaders, one of which is through the selection process with representatives from still classes and juran who have shown themselves to run as contestants. This is where the process of ahl al hal wal al aqd is implemented in the life of students in Islamic boarding schools to determine the leader in the organization.